STUDENT LEARNING INTEREST IN THE USE OF AUGMENTED REALITY MEDIA ON TRIANGLES AND QUADRILATERALS - Ilham Muhammad; Lilis Marina Angraini (IAIN Ambon, 2023)
Interactive multimedia is a learning model to generate thoughts, motivation, convey messages, and students' interests so as to encourage the teaching and learning process and the media is used to generate students' learning experiences to become more real. The purpose of the researchers conducting the research was to describe the interest in learning in students towards the use of Augmented media reality as learning media on triangle and quadrilateral material for class VII MTs. The researcher used a descriptive quantitative research method with 20 class VII MTs students as a random sample. This study used a non-test instrument in the form of a student learning interest questionnaire. Quantitative descriptive data analysis was used as a data analysis technique in this study. As for the results of student responses to the use of software Adobe Flash Cs6 Professional as a learning medium obtained a percentage with an average of 79.25% which is relatively high, this shows that students' responses to the use of Augmented media Reality as a positive learning media so that it can be used later for the learning process that can attract students' interest in learning